INSURANCE MARKETS IN RUSSIA AND KAZAKHSTAN: GENERAL FACTORS AND DEVELOPMENT POTENTIAL - Прокопьева, Евгения; Bykova, Valentina; Shelemetyeva, Olga (Scientific Journal of Pedagogy and Economics, 2021)
the article contains the problem of the development of insurance markets in geographically large countries by a comparative analysis of Russia and Kazakhstan in relation to the socio-economic development of the countries. Thus, based on the dynamics of macroeconomic indicators and the sectoral structure of the economies, the relationship between the indicators of insurance premiums and life insurance premiums with the overall development of the economy is revealed. On the basis of theoretical and empirical studies, it is revealed that the content of the socio-economic policy of the countries, the structure of the economy as a whole, as well as the mechanisms of functioning of the insurance markets are very similar. At the same time, the insurance market of Kazakhstan is somewhat behind the development of the insurance market of Russia, but has a more pronounced growth potential. According to the results of the study, the factors of economic development of the studied countries that affect the insurance market are identified, which are divided into stimulating and restraining by the nature of their influence. Further investigation of the identified factors will help to develop management solutions to improve the efficiency of the insurance markets of the two countries and integrate them into a single insurance space.